The Effectiveness Of Shampoo Based On Kaffir Lime Leave Extract (Citrus Hystrix DC) And Lime Leave (Citrus Aurantifolia) As Natural Protection Against Head Lice - Sjamsiah, Sjamsiah; Gani, Rahmiani; Febryanti, Amalyah; Gebriella, Gebriella; Mawaddah Warahmah, Nurul (Publisher Cv. Inara, 2025)
Pediculus humanus capitis is one of the problems that can interfere with human health. To overcome this, alternative treatments other than commercial shampoos are needed that can harm humans. The selection of shampoo from natural ingredients can be an alternative, namely Kaffir lime leaf shampoo (Citrus hystrix DC) and lime leaf shampoo (Citrus aurantifolia). The purpose of this study was to determine the characteristic properties of anti-head lice shampoo and determine the optimum concentration of kaffir lime leaf extract and lime leaf extract against head lice mortality. Based on the results of research for phytochemical screening show that the extract contains flavonoid compounds, saponins, alkaloids, triterpenoids, and tannins. The characteristics of shampoo preparations are that they have a blackish-green shampoo color, a distinctive aroma of orange leaves, and a thick form. In addition, a normal pH of 5-6, viscosity of 100-6000 cP, and foam height of 4-6 cm is obtained. Effectiveness tests against head lice were obtained at an optimum concentration of 5% for both kaffir lime leaf extract and lime extract. This shows the good potential of natural ingredients kaffir lime leaves and lime leaves as the basic ingredients of anti-shampoo lice.